Expect the unexpected. Issue 2 (April 2016) - Woo, Gordon
Abstract : Catastrophist Gordon Woo considers how airline risk assessors should respond to unusual threats to passenger safety Abstract : Egyptian authorities have conceded that October's Sinai plane crash was the work of terrorists.Gordon Woo considers how risk assessors might respond to these and other threats to passenger safety